Social selection parapatry in Afrotropical sunbirds. (1st June 2016) - McEntee, Jay P.; Peñalba, Joshua V.; Werema, Chacha; Mulungu, Elia; Mbilinyi, Maneno; Moyer, David; Hansen, Louis; Fjeldså, Jon; Bowie, Rauri C. K.
Abstract: The extent of range overlap of incipient and recent species depends on the type and magnitude of phenotypic divergence that separates them, and the consequences of phenotypic divergence on their interactions. Signal divergence by social selection likely initiates many speciation events, but may yield niche‐conserved lineages predisposed to limit each others' ranges via ecological competition. Here, we examine this neglected aspect of social selection speciation theory in relation to the discovery of a nonecotonal species border between sunbirds. We find that Nectarinia moreaui and Nectarinia fuelleborni meet in a ∼6 km wide contact zone, as estimated by molecular cline analysis. These species exploit similar bioclimatic niches, but sing highly divergent learned songs, consistent with divergence by social selection. Cline analyses suggest that within‐species stabilizing social selection on song‐learning predispositions maintains species differences in song despite both hybridization and cultural transmission. We conclude that ecological competition between moreaui and fuelleborni contributes to the stabilization of the species border, but that ecological competition acts in conjunction with reproductive interference. The evolutionary maintenance of learned song differences in a hybrid zone recommend this study system for future studies on the mechanisms of learned song divergence and its role in speciation.